KAJIAN AKSIOLOGI PEMEBELAJARAN BERBASIS DEEP LEARNING PADA PENDIDIKAN DASAR - Gufron, Iffan Ahmad; Suryahadikusumah, Ahmad Rofi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was motivated by public skepticism regarding the implementation of deep learning in education, particularly at the elementary level. The research aimed to examine the pedagogical benefits and ethical considerations of implementing deep learning through an axiological lens. A systematic literature review was conducted. The axiological analysis revealed that deep learning empowered students to develop a sense of belonging in their learning through critical thinking and reflection, fostering joyful, mindful, and meaningful learning experiences. The study highlights the importance of active, authentic, and collaborative learning, while also emphasizing the ethical considerations such as adaptability to digital learning environments and the quality of learning materials aligned with students' needs, interests, and life contexts.